PROJECT WORK “PICTURES ON THE PROGRAM INKSCAPE” - Yersultanova, Z.S.; Tanatova, M.; Duisenova, D. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
The article describes how to draw some elements in the INKSCAPE program. How to create an electronic application that is embedded in the WEB pages of the INKSCAPE software, using the HTML hypertext markup language. The result of creating an interactive application is shown.
Keywords: graphics; colors; tool; drawn; Inkscape; HTML; Web pages; tags